Special and Differential Treatment in the Area of Trade Facilitation - Moïsé, Evdokia (OECD Publishing, 2006)
Annex D of the July 2004 Decision of the WTO General Council indicates that "the principle (of special and differential treatment for developing and least-developed countries) should extend beyond the granting of traditional transition periods for implementing commitments. In particular, the extent and the timing of entering into commitments shall be related to the implementation capacities of developing and least-developed Members." The objective of this study is to offer reflections on how special and differential treatment for trade facilitation may be shaped by the cost implications of measures included in the future agreement. It is based on findings of OECD work on the costs of trade facilitation measures, which confirms that different countries - even at an equivalent level of development - face different situations and present differing implementation capacities, and points to the relative complexity of implementation of the different measures proposed for inclusion in a future trade facilitation agreement
Keywords: Trade